2018
DOI: 10.1186/s12879-018-3498-6
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol of the iMPaCT project: a longitudinal cohort study assessing psychological determinants, sexual behaviour and chlamydia (re)infections in heterosexual STI clinic visitors

Abstract: BackgroundChlamydia trachomatis (chlamydia), the most commonly reported sexually transmitted infection (STI) in the Netherlands, can lead to severe reproductive complications. Reasons for the sustained chlamydia prevalence in young individuals, even in countries with chlamydia screening programs, might be the asymptomatic nature of chlamydia infections, and high reinfection rates after treatment. When individuals are unaware of their infection, preventive behaviour or health-care seeking behaviour mostly depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…A detailed description of the study design can be found in the iMPaCT study protocol [19]. In short, the iMPaCT study explored the link between sexual behavior, psychological determinants, and chlamydia infections over a period of one year, using online questionnaires and information routinely registered by STI clinics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the study design can be found in the iMPaCT study protocol [19]. In short, the iMPaCT study explored the link between sexual behavior, psychological determinants, and chlamydia infections over a period of one year, using online questionnaires and information routinely registered by STI clinics.…”
Section: Methodsmentioning
confidence: 99%
“…For participants, additional data on behavioral and psychological data was available from the baseline online questionnaire. The development of the questionnaire has been described in detail in the iMPaCT study protocol [19]. Behavioral data included the number of sexual partners in the past six months, and age at sexual debut.…”
Section: Methodsmentioning
confidence: 99%
“…The protocol of the iMPaCT Study has been described in detail elsewhere (23). Briefly, selected individuals (heterosexuals aged 18–24 years and females aged 18–24 years who had sex with both men and women) who made an appointment at the STI clinic of Amsterdam, Kennemerland, Hollands Noorden, or Twente in the Netherlands between November 2016 and June 2017 were eligible to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral and psychological data were collected in the online questionnaire. This questionnaire was based on several validated questionnaires, which has been described elsewhere (23). Sexual behavior questions included number of sexual partners (lifetime/past 6 months/past 4 weeks) and age at first sexual activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation